Atherogenic lipidomics profile in healthy individuals with low cardiorespiratory fitness: The HUNT3 fitness study. (February 2022) - Nodeland, Markus; Klevjer, Marie; Sæther, Julie; Giskeødegård, Guro; Bathen, Tone Frost; Wisløff, Ulrik; Bye, Anja
Abstract: Background and aims: Low cardiorespiratory fitness is a strong and independent risk factor for cardiovascular disease (CVD). Serum profiling of healthy individuals with large differences in cardiorespiratory fitness may therefore reveal early biomarkers of CVD development. Thus, we aimed to identify circulating lipoprotein subfractions differentially expressed between groups of individuals with large differences in cardiorespiratory fitness, measured as maximal oxygen uptake (VO2max ). Methods: Healthy subjects (40–59 years) were selected from the third wave of the Trøndelag health study (HUNT3) based on having an age-dependent high VO2max (47.1 ± 7.7 mL kg −1 ·min −1, n = 103) or low VO2max (31.4 ± 4.9 mL kg −1 ·min −1, n = 108). The individuals were matched on gender, age, physical activity level and fasting status. Results: 99 lipoprotein subfractions were quantified in serum samples using nuclear magnetic resonance (NMR) lipidomics. Standard clinical analyses showed similar levels of total cholesterol, low-density lipoprotein (LDL)-cholesterol and high-density lipoprotein (HDL)-cholesterol between the groups, and slightly higher levels of triglycerides in participants with low VO2max . Thirteen lipoprotein subfractions were increased in the low VO2max group compared to the high VO2max group ( p  < 0.005), including mainly large very low-density lipoprotein (VLDL) subfractions. In addition, triglyceride levels in small-sized HDL and LDL particles were increased in participants with low VO2max . Correlation analyses between VO2max and lipoproteins subfractions displayed a negative correlation between VO2max and the levels of cholesterol and phospholipids in the small HDL particles. The lipoprotein profile of individuals with low VO2max is similar to the profile of insulin resistant individuals. Conclusions: Low VO2max was associated with enrichment of large VLDL particles, as well as an increased triglycerides content in the small and dense HDL and LDL particles. This unfavorable lipid profile is likely to be involved in the strong associations between VO2max and CVD. Graphical abstract: Image 1 Highlights: The circulating levels of very low-density lipoprotein (VLDL) subfractions were significantly higher in participants with low cardiorespiratory fitness (VO2max ) compared to participants with high VO2max. Triglyceride levels in small-sized high-density lipoprotein (HDL) and low-density lipoprotein (LDL) particles were higher in participants with low VO2max. When comparing healthy individuals with high and low VO2max, the lipoprotein subfraction profile of individuals with low VO2max showed similarities to the profile of insulin resistant individuals. The identified lipoprotein subfractions associated with VO2max may represent early risk markers of CVD development.